2020
DOI: 10.1186/s12936-020-03531-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of long-lasting insecticidal nets among women attending antenatal clinic at a tertiary hospital in Bayelsa State, Nigeria 2019

Abstract: Background Malaria in pregnancy remains a major contributor to maternal and infant morbidity and mortality despite scale up in interventions. Its prevention is one of the major interventions in reducing maternal and infant morbidity and mortality. The ownership, utilization and predictors of use of long-lasting insecticide-treated nets (LLINs) for malaria prevention among women attending antenatal clinic (ANC) at a tertiary hospital in Bayelsa State Nigeria was assessed. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several studies have shown that HIV during pregnancy amplifies the effects of malaria [9], which is why administering Cotrimozaxole alongside antiretroviral therapy (ART) to pregnant women is essential during every antenatal-care visit [9]. Nevertheless, there is enough evidence to show that, despite efforts such as the distribution of long-lasting insecticidal bednets (LLINs) to pregnant women [10] and the implementation of intermittent preventive treatment (IPT-p) programs to reduce the burden of these infections [11], co-infection among pregnant women remains a problem, as malaria during pregnancy persists among pregnant women [1,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that HIV during pregnancy amplifies the effects of malaria [9], which is why administering Cotrimozaxole alongside antiretroviral therapy (ART) to pregnant women is essential during every antenatal-care visit [9]. Nevertheless, there is enough evidence to show that, despite efforts such as the distribution of long-lasting insecticidal bednets (LLINs) to pregnant women [10] and the implementation of intermittent preventive treatment (IPT-p) programs to reduce the burden of these infections [11], co-infection among pregnant women remains a problem, as malaria during pregnancy persists among pregnant women [1,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%